Implementation of Authentic Assessment in English Listening Lessons at Junior High School - Fajar, Umul; Muamaroh; Halwat Hikmat, Mauly (LPPM Institut Studi Islam Sunan Doe, 2024)
The study explores the implementation of authentic assessment in English listening lessons within Junior High Schools under Indonesia’s Merdeka Curriculum. Employing a qualitative research method, the study involves interviews with English teachers in Sragen to gather insights into their experiences. The findings indicate that teachers utilize various assessment types, such as diagnostic, formative, and summative assessments, integratred into the learning process. Despite the benefits of authentic assessment, including improved listening skills and real-world application, teachers face challenges such as limited time, resources, and confidence in implementing these assessments. The research highlights the necessity for comprehensive support and professional development to optimize the use of authentic assessment in enhancing students’ listening skills.